2012
DOI: 10.1002/pola.26299
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of networked polymer based on ring‐opening addition reaction of 1,3‐benzoxazine with resorcinol

Abstract: A highly efficient ring-opening addition reaction of benzoxazine at ambient temperature has been developed with 2-methylresorcinol as a nucleophilic reagent. In this reaction, 2-methylresorcinol reacted with two equivalent amount of benzoxazine to give the corresponding 1:2 adduct, demonstrating its potential as a bifunctional nucleophile. Based on this reaction, a new crosslinking system consisting of a polymer bearing benzoxazine moieties in the side chains and 2-methylresorcinol as a crosslinker has been pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32] To cure 1,3-benzoxazines, thermally accelerated polymerization has been the main focus for most researchers for a long time. To date, very few compounds, including phenolic compounds, [39][40][41][42][43][44] thiols, [45][46][47][48][49] benzimidazoles, 50 benzoxazoles, 26,51,52 chitosan ammonium, 53 and some polymers containing aromatic structures 19,21,23 have been reported to construct chemical linkages with benzoxazines. 19,20,[33][34][35] The basic concept of the reaction mechanism is the protonation of the oxygen atom in the oxazine ring, followed by the formation of a zwitter iminium ionic structure, and its subsequent Scheme 1 The polymerization mechanisms of benzoxazine proposed by previous reports.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32] To cure 1,3-benzoxazines, thermally accelerated polymerization has been the main focus for most researchers for a long time. To date, very few compounds, including phenolic compounds, [39][40][41][42][43][44] thiols, [45][46][47][48][49] benzimidazoles, 50 benzoxazoles, 26,51,52 chitosan ammonium, 53 and some polymers containing aromatic structures 19,21,23 have been reported to construct chemical linkages with benzoxazines. 19,20,[33][34][35] The basic concept of the reaction mechanism is the protonation of the oxygen atom in the oxazine ring, followed by the formation of a zwitter iminium ionic structure, and its subsequent Scheme 1 The polymerization mechanisms of benzoxazine proposed by previous reports.…”
Section: Introductionmentioning
confidence: 99%
“…Several effective and even efficient catalysts and initiators were developed to reduce the curing temperature of benzoxazines. Initiators are usually Lewis acids like phosphorus pentachloride, titanium chloride, and aluminum chloride, carboxylic acids like trifluoroacetic acid and sebacic acid, alcohols like p ‐cresol and 2‐methylresorcinol, thiols like benzylthiol, metal complexes like acetylacetonato‐complexes with iron, manganese, or cobalt, sulfonates like p ‐toluenesulfonate, salts like lithium iodide, and photolatent onium salts like diphenyliodonium and triphenylsulfonium salts . Examples for really efficient known benzoxazine/initiator systems and their respective curing temperatures (measured by DSC) are BA‐a/PCl 5 with T c of 122 °C, p C‐a/LiI with T c of 197 °C, p C‐a/Zn(OTf) 2 with T c of 199 °C, and p C‐a/ p ‐toluenesulfonates with T c of 100–120 °C (not measured by DSC) …”
Section: Introductionmentioning
confidence: 99%
“…They may also show different reactivity toward benzoxazines. Recently, Oie et al demonstrated a new approach to form polybenzoxazines due to ring‐opening addition . This reaction of a benzoxazine ring with 2‐methylresorcinol occurs at ambient conditions and is therefore a promising concept.…”
Section: Introductionmentioning
confidence: 99%
“…Burke [22] reported addition reaction of benzoxazines with phenols that proceeded to giving the corresponding adducts. Oie et al [23] also reported networked polymers were synthesized by the additional reaction of benzoxazine and resorcinol. Thus, similar reaction of benzoxazine and phenols should exist in present resins.…”
Section: Curing Reaction Of Ba/13-pbo/hppe Resinsmentioning
confidence: 99%